The Functional Difficulties Questionnaire: A New Tool for Assessing Physical Function of the Thoracic Region in a Cardiac Surgery Population. Issue 3 (July 2018) - Sturgess, Tamica R.; Denehy, Linda; Tully, Elizabeth A.; McManus, Margaret; Katijjahbe, Mohd Ali; El-Ansary, Doa
Abstract : Purpose: There is a paucity of functional outcome measures that specifically target the thoracic region and none that are specific for use in people following cardiac surgery. The aim of this study was to develop a functional questionnaire for this purpose and investigate its psychometric properties. Methods: Participants who underwent cardiac surgery were included in this single-site, observational study (part A, n = 38 and part B, n = 25). The investigators developed a 13-item Functional Difficulties Questionnaire (FDQ) informed by the literature, theory, and clinical practice. The questionnaire and measures of physical function, pain, and health-related quality of life (HRQOL) were completed at 4 time points by 38 participants to investigate internal consistency, convergent validity, and responsiveness to change of the FDQ (part A). A different group of 25 participants completed the questionnaire twice within a single day to investigate test–retest reliability, and minimal detectable change (MDC) was calculated (part B). Results: The questionnaire showed good internal consistency (Cronbach alpha coefficient = 0.971); moderate to good correlation with assessments for HRQOL 3 months postoperatively (rho = 0.54–0.65 for 5 36-Item Short Form Health Survey subscales) and total pain at all postoperative time points (rho = 0.55–0.69); a responsiveness to change with significant differences in scores across time (Χ 2 [3, n = 38] = 41.37, P ⩽ 0.0001); and excellent test–retest reliability (intraclass correlation 0.918). The MDC was 16.35 cm out 130 cm. Conclusions: The FDQ is an appropriate functional outcome measure specific to the thoracic region for people after cardiac surgery. It may also be suitable for use by clinicians and researchers assessing the thoracic region within other surgical or medical populations, and this warrants further investigation.